OP57 Cost effectiveness analysis of a UK legislative ban on dietary industrial trans fats: modelling study. (2nd September 2014) - Pearson-Stuttard, J; Hooton, W; Collins, M; Mason, H; Critchley, J; Capewell, S; O'Flaherty, M
Abstract : Background: Coronary heart disease (CHD) remains a leading cause of UK mortality, generating a large and unequal burden of disease. CHD costs the UK in excess of £6 billion annually, with estimated statins costs exceeding £840 million. Dietary trans fats represent a powerful CHD risk factor. However, UK efforts to reduce intake (currently approximately 1% of daily energy) have been less successful than some other nations, such as Denmark and the USA. Furthermore, the potential heath and economic outcomes of a legislative ban, and the effects upon health inequalities, have not been well quantified. We therefore aimed to model the potential health and economic effects of a UK legislative ban on industrial trans fats up to 2030. Methods: We extended the previously validated IMPACTsec model, to estimate the potential effects of a ban on dietary industrial trans fats upon the England and Wales population aged over 25 years. We stratified these estimates by age, sex and socio-economic circumstances. Data sources included Hospital Episode Statistics, General Practice Registry Database, and Office of National Statistics. Cost data was sourced from Department of Health, NICE and British Retail Consortium. We estimated the subsequent economic effects of a legislative ban upon healthcare, informal care, productivity, and industry and the disease burden (expected CHD deaths, life years gained (LYGs), Quality adjusted life years (QALYs) and hospital admissions) over a 15 year horizon to 2030. The baseline results were tested in a probabilistic sensitivity analysis. Results: A legislative ban on industrial trans fats across the England and Wales population, reducing intake to 0.5% of daily energy intake would result in approximately 5468 fewer deaths per year, (95% confidence intervals (CI) 5459–5477), with some 6000 fewer hospital admissions (95% CI 5300–6700); and gaining approximately 43, 400 additional life years (95% CI 43, 200–43, 700). This would also reduce health inequalities, having a substantially larger beneficial effect upon mortality and LYGs in the most deprived, than the most affluent. A legislative ban could result in savings in excess of approximately £2 billion and generate gains of over 400, 000 QALYs over a 15 year period. This would include annual savings of approximately £16 million in direct healthcare costs, some £50 million productivity gains and approximately £70 million savings in informal care costs. Industry reformulation costs would be relatively small. Conclusion: Eliminating the UK dietary intake of industrial trans fats could substantially decrease CHD mortality, whilst also resulting in substantial savings annually. Urgent fiscal or legislative action is warranted.